Contemporary treatment of anxiety in primary care: a systematic review and meta-analysis of outcomes in countries with universal healthcare - Erin L. Parker; Michelle Banfield; Daniel B. Fassnacht; Timothy Hatfield; Michael Kyrios (BMC Family Practice, 2021)
Abstract Background Anxiety disorders are highly prevalent mental health conditions and are managed predominantly in primary care. We conducted a systematic review and meta-analysis of psychological and pharmacological treatments in countries with universal healthcare, and investigated the influence of treatment provider on the efficacy of psychological treatment. Method PubMed, Cochrane, PsycINFO, CINAHL, and Scopus were searched in April 2017 for controlled studies of evidence-based anxiety treatment in adults in primary care, published in English since 1997. Searches were repeated in April 2020. We synthesised results using a combination of meta-analysis and narrative methods. Meta-analysis was conducted using a random-effects multi-level model to account for intercorrelation between effects contributed different treatment arms of the same study. Moderator variables were explored using meta-regression analyses. Results In total, 19 articles (from an initial 2,247) reporting 18 studies were included. Meta-analysis including ten studies (n = 1,308) found a pooled effect size of g = 1.16 (95%CI = 0.63 – 1.69) for psychological treatment compared to waitlist control, and no significant effect compared to care as usual (p = .225). Substantial heterogeneity was present (I2 = 81.25). Specialist treatment produced large effects compared to both waitlist control (g = 1.46, 95%CI = 0.96 – 1.96) and care as usual (g = 0.76, 95%CI = 0.27 – 1.25). Treatment provided by non-specialists was only superior to waitlist control (g = 0.80, 95%CI = 0.31 – 1.28). We identified relatively few studies (n = 4) of medications, which reported small to moderate effects for SSRI/SNRI medications and hydroxyzine. The quality of included studies was variable and most studies had at least “unclear” risk of bias in one or more key domains. Conclusions Psychological treatments for anxiety are effective in primary care and are more effective when provided by a specialist (psychologist or clinical psychologist) than a non-specialist (GP, nurse, trainee). However, non-specialists provide effective treatment compared with no care at all. Limited research into the efficacy of pharmacological treatments in primary care needs to be considered carefully by prescribers Trial registration PROSPERO registration number CRD42018050659